Virologic suppression and mortality of patients who migrate for HIV care in the province of British Columbia, Canada, from 2003 to 2012: a retrospective cohort study - Lima, Viviane Dias (BMC Health Serv Res, 2015)
BACKGROUND: Migration among persons living with HIV (PLWH) seeking HIV care is common; however its effect on health outcomes in resource-rich settings is not well understood. We conducted a retrospective cohort study to quantify the extent to which PLWH are migrating for care within British Columbia (BC) and its association with virologic suppression and mortality. METHODS: Eligible PLWH first initiated treatment in BC between 2003 and 2012 (N = 3653). Analyses were performed at the regional Health Authority (HA) level (N = 5). For privacy reasons, we kept the name of these HAs anonymous and we re-named these five regions as 1 to 5. PLWH were classified according to the HA where they resided and received HIV care. We calculated all-cause mortality rates, life expectancies (at age of 20 years), and in, out and net migration rates across HAs using different demographic methods. Virologic suppression (<50 copies/mL) was based on the last viral load available for each PLWH. We also calculated per-capita rates (per 100 PLWH ever on cART) for each HA by dividing the number of PLWH by the number of physicians attending this population. RESULTS: There is considerable heterogeneity in physician availability across all HAs, with per-capita rates (per 100 PLWH ever on cART) ranging from 2.2 (HA 1) to 12.7 (HA 3) based on the HA PLWH received care. We observed that in HAs 1, 4, and 5, between 4 and 10 % of PLWH migrated to HA 3 (i.e. the largest urban center) to receive care, and for HA 2 this proportion increased to 21 %. In HA 3, 77 % of its PLWH residents remained in the same HA for their care. Migrating to a larger center for HIV care was not associated with higher rates of viral load suppression; it was significantly associated with lower mortality rates and higher life expectancies. CONCLUSIONS: A thorough understanding of the reason(s) for these significant migration rates across BC will be critical to inform resource allocation and optimize the impact of HIV treatment.